2020
DOI: 10.3390/w12082133
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Approach to the Spatial and Statistical Analysis of Factors Influencing Spring Distribution on a Transboundary Karst Aquifer

Abstract: Karst aquifers are indispensable, yet vulnerable, resources; therefore, they require a comprehensive protection strategy. Since springs are the terminal points of the karst flow systems, knowledge of their distribution is a key element for the better understanding of groundwater flow, availability and vulnerability. The present study aims to introduce a data-driven analysis by the application of a spatial statistical technique (Weights of Evidence (WofE)) for the evaluation of factors influencing spring distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…3, March, 2024 1132 village in DKI Jakarta. A P-value smaller than 0.01 indicates the variable significance of the area area and the number of polling stations is very significant (Iván, Stevenazzi, Pollicino, Masetti, & Mádl-Szőnyi, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…3, March, 2024 1132 village in DKI Jakarta. A P-value smaller than 0.01 indicates the variable significance of the area area and the number of polling stations is very significant (Iván, Stevenazzi, Pollicino, Masetti, & Mádl-Szőnyi, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that the occurrence of springs is the result of many spatial factors [2,[6][7][8][9][10], which is why it is difficult to predict their exact locations. Despite technological progress and the use of remote sensing in spring research [11][12][13][14], it is still relatively difficult to determine the exact locations of springs without proper fieldwork, especially in the case of relatively small springs, considering their size and discharge. For this reason, studies of mountain springs often require extensive fieldwork, especially for their mapping [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…They indicate the end of underground river systems and the transition from surface uvial activities to surface uvial processes (Ford & Williams, 2007). As a result, springs exert major control over the operation of karst groundwater bodies (Iván et al, 2020). The distribution of springs is important for a better understanding of not just ow, but also karstic characteristics and groundwater susceptibility (Ghadimi et al, 2022;Iván and Mádl-Szőnyi, 2017;Zwahlen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(Ozdemir, 2011) showed the LR model approach was employed to determine probable zones for groundwater springs in the Sultan Mountains in Turkey. (Iván et al, 2020) used the WE method to estimate the location of springs in Gömör-Torna in Eastern Europe. This method was used to provide a quantitative comprehension of the geological and structural conditions that support spring development.…”
Section: Introductionmentioning
confidence: 99%